(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the theoretical foundations and methodological approaches to teaching reading in a foreign language within higher education. Drawing upon national and international scholarship in psycholinguistics, pedagogy, and TESOL methodology, the study systematizes key conceptualizations of reading as a multi-level cognitive and communicative process. Particular attention is given to the works of L.V.Shcherba, Z.I.Klychnikova, A.R.Luria, A.N.Shchukin, and Benjamin Bloom, whose research has shaped understanding of reading mechanisms, levels of comprehension, and cognitive development. The study employs theoretical and comparative analysis of methodological literature, synthesis of psychological and pedagogical classifications, and taxonomic analysis based on Bloom’s hierarchy of cognitive skills. The findings demonstrate that reading comprehension develops across multiple cognitive levels, from lexical recognition to deep interpretative and evaluative processing. The paper identifies core mechanisms of reading, including motivational activation, semantic processing, and comprehension monitoring. It also systematizes classifications of reading types (skimming, scanning, detailed, and critical reading) and highlights the pedagogical significance of critical reading for academic literacy development.